2021
DOI: 10.1021/acs.jpclett.1c01810
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of Polyatomic Molecules in Dark Clouds: CO2 Formation on Cold Amorphous Solid Water

Abstract: Understanding the formation of molecules under conditions relevant to interstellar chemistry is fundamental to characterize the chemical evolution of the universe. Using reactive molecular dynamics simulations with model-based or high-quality potential energy surfaces provides a means to specifically and quantitatively probe individual reaction channels at a molecular level. The formation of CO2 from collision of CO­(1Σ) and O­(1D) is characterized on amorphous solid water (ASW) under conditions typical in col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 47 publications
2
17
0
Order By: Relevance
“…Finally, heating of the water molecules occurs on the 10 ps time scale following the recombination reaction. Consistent with earlier work, ( Fredon et al, 2021 ; Upadhyay et al, 2021 ), no CO 2 desorption is found from the simulations carried out here.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Finally, heating of the water molecules occurs on the 10 ps time scale following the recombination reaction. Consistent with earlier work, ( Fredon et al, 2021 ; Upadhyay et al, 2021 ), no CO 2 desorption is found from the simulations carried out here.…”
Section: Discussionsupporting
confidence: 93%
“…Relaxation of the angle occurs within the following 50 ps and the CO 2 molecule remains in an internally excited state on much longer time scales, see Figure 2C . ( Upadhyay et al, 2021 ). Concomitantly, the average internal energy of the surrounding water molecules increases by about 10%, see black, red and green traces in Figures 2D,E .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations